Diagnostic Accuracy and Safety of Teledermoscopy for Cutaneous Melanoma Triage in Northern Sweden - Virginia Zazo; Antonia Boman; Nirina Andersson (Acta Dermato-Venereologica, 2024)
Abstract is missing (Short communication)